НАРОДНЫЕ ПОСЛОВИЦЫ И ПОГОВОРКИ И ИХ ИСПОЛЬЗОВАНИЕ НА УРОКАХ (Scientific journal of the Fergana State University, 2023)
This article discusses the role of proverbs and sayings and  importance of using  them during the lesson